Hungary : 2013 Article IV Consultation and Third Post Program Monitoring Discussions-Staff Report; Informational Annex; Public Information Notice; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2013)
This paper presents 2013 Article IV Consultation and Third Post Program Monitoring discussions on Hungry. While the output gap remains sizable, inflation expectations are not well anchored, and after seven consecutive policy rate cuts a pause seems prudent. Further monetary policy easing can be supported by stronger macroeconomic policies. Some efforts have been made to improve labor participation, but potential growth remains far too low for a country that should converge faster to EU-average incomes. The IMF report suggests that maintaining market confidence and reviving growth are the most pressing priorities for which decisive action to improve policies is needed.